HOLDITCH-TYPE THEOREMS FOR THE POLAR MOMENT OF INERTIA UNDER THE 1-PARAMETER CLOSED PLANAR HOMOTHETIC MOTION - Akar, Mutlu; Yuce, Salim (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2021)
In this study, during the 1-parameter closed homothetic motion, the Holditch-Type Theorems are presented for the polar moments of inertia of the closed orbit curves of three non-collinear points.
Keywords: Holditch Theorem; Homothetic Motion; Polar Moment of Inertia; Science & Technology - Other Topics